Evaluation of the Effects of Ulnar Artery Flow and Allen’s Test on Radial Artery Graft Preference - İlkeli, Ekin; Toz, Ali Cemal; Uysal, Ayhan (My University, 2021)
Objective: This study is to evaluate the efficacy of preoperative and postoperative ulnar arterial flows and preoperative Allen’s test in using radial artery graft once coroner bypass surgery. Material and Method: We retrospectively analyzed the data of 30 patients who underwent coronary bypass surgery and the radial artery was used as a graft. Arterial Doppler ultrasonography was performed before and after coronary bypass surgery, and the preoperative modified Bedford Allen test was applied to all patients preoperatively. A radial artery graft was used all patients. It was understood from the records that the ulnar artery flows in the postoperative period were controlled by Doppler ultrasonography at the 3rd and 6th months. Ulnar artery diameter and flow velocities were com-pared with preoperative Doppler ultrasonography data. Results: There was an increase in flow and velocity measurements in ulnar artery after use of radial artery as a graft. The flow of mean ulnar artery increased from 31 ± 21 ml/min to 46±32 ml/min, and the mean speed of ulnar artery increased from 56±19 cm/sec to 78±16 cm/sec (p <0,005). En-hanced ulnar artery diameters and flows were detected in the postoperative 3rd and 6th periods of Doppler USG (p <0.005). In the postoperative follow up, there was no hand ischemia. Conclusion: Ulnar artery Doppler ultrasonography and allen testing is a reliable option in coronary bypass surgery to prevent arm ischemia after revascularization with radial artery graft.
Keywords: Periferik Damar Hastalıkları; Sağlık Bilimleri ve Hizmetleri; Kalp ve Kalp Damar Sistemi; Cerrahi